Integrasi Pendidikan Karakter Dalam Penerapan Blended Learning Di Sekolah Dasar - Dewa Made Dwicky Putra Nugraha (Cetta: Jurnal Ilmu Pendidikan, 2020)
This study aims to describing character education in the application of blended learning in elementary schools. The other purpose of this study is to formulate character education activities suitable for integration into blended learning in elementary schools. The research method used is library research (Library Research). Data collection techniques applied in this discussion are reviewing books, research journals, literature, and other documents deemed relevant to the research problem. The findings in the data collection process are documented for later analysis and presented descriptively. The results of this study are; 1) a study of character education in elementary schools, 2) a study of the application of blended learning in elementary schools, and 3) description of integrating character education in the application of blended learning in elementary schools.